PENGARUH PROGRAM PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN - Julianita, Rizska (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2018)
This research is intended to find out how the influence of Career Development on Employee Performance PT Bumi Andalas Permai (BAP) Palembang. In this case the sampling using the Saturated sampling method with the employee population of PT BAP Palembang as many as 78 people. From the results of the questionnaire, processed by using SPSS for Windows version 19 by using simple linear regression method, hypothesis test (t test), and correlation coefficient.Based on the analysis results obtained coefficient (R) of 0.033 which shows the relationship between the two low variables. In the hypothesis test (t test) obtained t count value of -0.285 and t value table 1.991, and significant value 0.777. And when viewed from the probability (sig), career development has a probability value of 0.777. It has also been explained that 0.777> 0.05, then H1 is rejected and H0 is accepted, indicating there is no effect of career development on employee performance. The effect of career development on employee performance can be seen also from the value of regression coefficient (R) 0,001, which shows that the percentage contribution of career development influence to employee performance equal to 0,1%. Can also be interpreted that the variation of career development variables used to explain 0.1% variation of performance variables. The conclusion : career development program does not effect employee performance on PT BAP Palembang.